2021
DOI: 10.1038/s41526-021-00131-1
|View full text |Cite
|
Sign up to set email alerts
|

The combined effects of simulated microgravity and X-ray radiation on MC3T3-E1 cells and rat femurs

Abstract: Microgravity is well-known to induce Osteopenia. However, the combined effects of microgravity and radiation that commonly exist in space have not been broadly elucidated. This research investigates the combined effects on MC3T3-E1 cells and rat femurs. In MC3T3-E1 cells, simulated microgravity and X-ray radiation, alone or combination, show decreased cell activity, increased apoptosis rates by flow cytometric analysis, and decreased Runx2 and increased Caspase-3 mRNA and protein expressions. In rat femurs, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Female BALB/cByJ 4-month-old mice were exposed to low dose and high LET silicon ion radiation (0.17 Gy single radiation, 0.5 Gy single radiation and fractionated radiation) under partial weightlessness (G/6 to simulate lunar gravity). It was noted that the combination of the two factors had a negative effect on the maintenance of bone mass by both reducing bone formation and increasing bone resorption, and the impaired bone formation response was related to the inhibited Wnt signaling ( Macias et al, 2016 ), the increased Runx2 and decreased Caspase-3 mRNA expression ( Dong et al, 2021 ). On the whole, most studies showed that microgravity-induced bone loss and impaired bone mechanical properties were aggravated by ionizing radiation exposure.…”
Section: Combined Biological Effects Of Space Environmental Factors I...mentioning
confidence: 99%
“…Female BALB/cByJ 4-month-old mice were exposed to low dose and high LET silicon ion radiation (0.17 Gy single radiation, 0.5 Gy single radiation and fractionated radiation) under partial weightlessness (G/6 to simulate lunar gravity). It was noted that the combination of the two factors had a negative effect on the maintenance of bone mass by both reducing bone formation and increasing bone resorption, and the impaired bone formation response was related to the inhibited Wnt signaling ( Macias et al, 2016 ), the increased Runx2 and decreased Caspase-3 mRNA expression ( Dong et al, 2021 ). On the whole, most studies showed that microgravity-induced bone loss and impaired bone mechanical properties were aggravated by ionizing radiation exposure.…”
Section: Combined Biological Effects Of Space Environmental Factors I...mentioning
confidence: 99%
“…Congruent to spaceflight observations, most of the current literature consistently suggest that simulated-µG inhibits the proliferation and differentiation of MSC towards osteoblasts, despite using different methods of µG simulation (Table 5). This is indicated by the suppressed gene expression of osteoblast differentiation markers such as bone morphogenic protein (BMP) and Runt-related transcription factor 2 (Runx2) 18,[90][91][92][93][94][95][96][97][98][99][100][101] , in addition to the lowered expression of other osteoblastogenesis-related genes 18,97,99,[101][102][103] . The marker for osteoblast maturation from MSC progenitors -ALP, is also expressed at lower levels in preosteoblasts and osteoblasts exposed to various forms of simulated-µG [95][96][97]99,104 .…”
Section: Cell Type/ Speciesmentioning
confidence: 99%
“…It is suggested that simulated-µG prevents extracellular calcium from entering osteoblasts, thus reducing intracellular free calcium levels which impairs calcium deposition and bone formation 102,106 . Furthermore, simulated-µG has been shown to cause cell cycle arrest at G2 and even induce apoptosis in osteoblasts 100,102 . HLUinduced bone loss in mice is consistently accompanied by a reduction in the number of viable osteoblasts and osteocytes in mice 107 .…”
Section: Cell Type/ Speciesmentioning
confidence: 99%